Thermal properties of solid solution of manganese (II) -cobalt (II) diphosphate - Antraptseva, N.M.; Solod, N.V. (Functional Materials, 2016)
The composition, temperature ranges of formation and thermal stability of heat treatment products of solid solution with the general formula (Mn₁-xCox)₂P₂O₇•5H₂O (0 leq; x≤0.41) in the range of 298-1273 K were determined. The cation nature effect on them was concretized. The end product of the heat treatment - solid solution of anhydrous diphosphates with composition β-(Mn₁-xCox)₂P₂O₇, 0 &leq& x≤ 0.41 (space group C 2/m, Z = 2) - was identified. It was shown, that its formation is realized in two directions. The first of them is realized by 69-66 % due to dehydration of initial crystallohydrate (Mn₁-xCox)₂P₂O₇•5H₂O. According to the second direction, 31-34 % β-(Mn₁-xCox)₂P₂O₇ is formed through solid phase reaction of the intermediate dehydration products. The sequence of thermal and structural transformations, which accompany the heat treatment of the diphosphates (Mn₁-xCox)₂P₂O₇•5H₂O (0 ≤x≤0.41), was proposed.